2020
DOI: 10.3390/jcm9124094
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Human Embryo Metabolic Assessment as a Developmental Criterion

Abstract: The selection of a highly-viable single embryo in assisted reproductive technology requires an acceptable predictive method in order to reduce the multiple pregnancy rate and increase the success rate. In this study, the metabolomic profiling of growing and impaired embryos was assessed on the fifth day of fertilization using capillary electrophoresis in order to find a relationship between the profiling and embryo development, and then to provide a mechanistic insight into the appearance/depletion of the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Another significantly increased concentration was found for Gln, which was associated with higher development stages, differences were found between unfertilized oocytes compared to well‐developing embryos up to 8‐cell embryos or embryos that reached the morula or blastocyst stage: (4)–(2), (4)–(1); and also between embryos that failed to develop or well‐developing embryos up to 8‐cell embryos compared to embryos that reached the morula or blastocyst stage: (3)–(1), (2)–(1). Elevated Gln levels were reported in the literature [7,12,27,33,34]. On the other hand, Gln consumption was also reported [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another significantly increased concentration was found for Gln, which was associated with higher development stages, differences were found between unfertilized oocytes compared to well‐developing embryos up to 8‐cell embryos or embryos that reached the morula or blastocyst stage: (4)–(2), (4)–(1); and also between embryos that failed to develop or well‐developing embryos up to 8‐cell embryos compared to embryos that reached the morula or blastocyst stage: (3)–(1), (2)–(1). Elevated Gln levels were reported in the literature [7,12,27,33,34]. On the other hand, Gln consumption was also reported [35].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the combination of CE with MS detection offers the definitive identification of metabolites and also the identification of new metabolic targets. So far CE has been used for the analysis of lactate, pyruvate, and AAs in spent media with conductivity and LIF detection [7,26,27]. Besides this, CE-MS was used for the single-cell metabolomic analysis of frog Xenopus laevis embryos [28] and there were recently published several reviews on CE-MS for metabolomics [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…However, as a precaution against possible toxicity, glutamine is almost universally added to embryo culture media in the form of a dipeptide; usually, alanyl glutamine or glycyl glutamine, which can replace glutamine in [ 70 , 71 ]. Motiei et al [ 72 ] recently reported that these dipeptides are depleted from the culture medium of viable embryos. It is presumed that they are taken up intact by the embryo and hydrolysed intracellularly to provide glutamine and the companion amino acid, though some may be broken down by extracellular, vesicle-derived peptidases released by the embryo.…”
Section: Ammonia Productionmentioning
confidence: 99%
“…Until the morula stage, cell divisions are said to be reductive because they take place at constant embryonic volume within the zona pellucida (around 120 µm). From day 4, embryo metabolism switches towards the consumption of glucose and amino acids [ 71 , 72 ].…”
Section: Comparative Anatomical Physiological and Pathological Aspects Of Reproduction In Mares And Womenmentioning
confidence: 99%